Implementation of the Merdeka Curriculum in 3T Areas: A Study at Orasi Indo Sinasih Private Junior High School, Silau Kahean District, Simalungun Regency, North Sumatra Province - Tondang, Rika Sinta; Nurdiyana, Nurdiyana (Universitas Pamulang, 2026)
Research on the implementation of the Independent Curriculum in the 3T (Underdeveloped and Disadvantaged Regions) at Orasi Indo Sinasih Private Junior High School, Silau Kahean District, Simalungun Regency, North Sumatra Province, provides flexibility for educators in designing learning that is tailored to the needs and characteristics of students, as well as local conditions. This study aims to determine the implementation of the Independent Curriculum in the 3T (Underdeveloped and Disadvantaged Regions) areas, specifically at Orasi Indo Sinasih Private Junior High School, Silau Kahean District, Simalungun Regency, North Sumatra Province. This study used a qualitative approach with descriptive methods. The research subjects consisted of the principal and teachers. Data collection techniques included observation, interviews, and documentation. Data analysis techniques used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that the Independent Curriculum has been implemented quite well, although obstacles remain, such as limited infrastructure, low technology utilization, and the community's socioeconomic conditions. Principals play an active role in developing strategies to improve educational quality, such as teacher training, implementing project-based learning, and strengthening student character through the values of the Pancasila Student Profile. The conclusion of this study is that the Independent Curriculum can be implemented effectively in 3T (third-to-third) areas and can be a solution to improving educational quality in these areas if accompanied by optimal support from all parties.